2020
DOI: 10.1186/s13601-020-00331-0
|View full text |Cite
|
Sign up to set email alerts
|

The disease burden in patients with respiratory allergies induced by house dust mites: a year-long observational survey in three European countries

Abstract: Background: House dust mite (HDM) allergens constitute the most frequent cause of persistent allergic rhinitis and asthma. The symptoms vary throughout the year but typically peak in spring, autumn and (to a lesser extent) midwinter. Methods: We performed a 13-month, observational, multicentre survey of adult patients with a self-reported history of moderate-to-severe, poorly controlled, physician-diagnosed HDM respiratory allergy in three European countries (France, Italy and Spain). After screening and inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 24 publications
0
18
0
1
Order By: Relevance
“…The prompt improvement was observed even though the cats were enrolled at different times of the year, so that seasonal variations in the concentrations of environmental mites were expected. 24 This trend continued throughout the study to the 12 month end-point.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The prompt improvement was observed even though the cats were enrolled at different times of the year, so that seasonal variations in the concentrations of environmental mites were expected. 24 This trend continued throughout the study to the 12 month end-point.…”
Section: Discussionmentioning
confidence: 79%
“…Although more studies are required to assess differences with other species, the oral route was fast‐acting in the cats included in our study because clinical improvement was observed during the first three months of treatment in the vast majority of them [SCORFAD values improved in almost all included cats (19 of 22) and pVAS scores improved in 17 cats (Figures S2 and S3)]. The prompt improvement was observed even though the cats were enrolled at different times of the year, so that seasonal variations in the concentrations of environmental mites were expected 24 . This trend continued throughout the study to the 12 month end‐point.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 22 995 individuals were screened; 339 of these (1.5%) were included and 313 ( n = 114 in Italy, 92 in France, and 107 in Spain) completed the fortnightly study phase and the post-inclusion questionnaire. 12 , 13 The baseline characteristics of the study population have been published in our initial report on the study but are summarized here for convenience ( Supplemental Table 1 ). 12 , 13 As reported previously, the majority of participants (61% in Italy, and 79% in France and Spain) reported having another physician-diagnosed respiratory allergy (mainly due to grass pollen, followed by weed pollen, pet dander, and tree pollen).…”
Section: Resultsmentioning
confidence: 99%
“…In order to better characterize HDM-induced respiratory allergies from the patient's perspective, we performed a 13-month, observational, multicenter, Internet- and telephone-based survey of adult patients with a self-reported history of moderate-to-severe, poorly controlled, physician-diagnosed HDM respiratory allergy (but no other physician-diagnosed respiratory allergies) in 3 European countries (France, Italy, and Spain) from late May 2012 to early July 20, 13. 12 , 13 Briefly, a total of 22 995 people were screened; 339 were included in the study, and 313 (n = 114 in Italy, 92 in France, and 107 in Spain; 67% females, with a predominance of young adults; mean age: 37.2 years) completed the fortnightly telephone interview phase and the post-inclusion questionnaire. The study generated a large amount of data, some of which has already been reported: the study's methodology, the participants' baseline demographic and clinical characteristics, the changes in symptom prevalence and intensity, the disease burden, and medication use.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation